2019
DOI: 10.1101/581025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ROS accumulation and associated cell death mediates susceptibility to Alternaria brassicae in Arabidopsis accessions

Abstract: Alternaria brassicae is a necrotrophic fungal pathogen capable of infecting most of the agriculturally important Brassica species. The mechanisms underlying invasion of A. brassicae and host responses are unknown. In the present study, we exploited the natural variation in Arabidopsis to understand the molecular and cellular mechanisms underlying resistance to A. brassicae. Using a subset of resistant (Ei-2, Ull2-3, Lz-0, and Cvi-0) and susceptible (Gre-0, Est-1, and Zdr1) accessions, we show that the suscepti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous studies on the infection of A. brassicae have identified two critical time points viz. 2 and 4 days post infection [6], therefore we studied the expression of AbrNLP1 and AbrNLP2 at these time points. We found that both AbrNLP1 and AbrNLP2 are expressed in vitro i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the infection of A. brassicae have identified two critical time points viz. 2 and 4 days post infection [6], therefore we studied the expression of AbrNLP1 and AbrNLP2 at these time points. We found that both AbrNLP1 and AbrNLP2 are expressed in vitro i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Cell death (either necrotic or apoptotic-like) plays a central role in plant-pathogen interactions either by restricting pathogen growth (in case of biotrophs) or by providing a nutrient source for the proliferation of the pathogen (in case of necrotrophs). Many well-known necrotrophic pathogens such as Botrytis cinerea, Sclerotinia sclerotiorum, Alternaria brassicae have been shown to induce cell death in the host and effective induction of cell death leads to susceptibility [6-8].…”
Section: Introductionmentioning
confidence: 99%